Initial Analysis of the Second FIG 3D Cadastres Questionnaire :Status in 2014 and Expectations for 2018 - OOsterom, Peter Van (2020)
http://www.gdmc.nl/3DCadastres/workshop2014/programme/Workshop2014_04.pdf